2017
DOI: 10.5603/aa.2016.0014
|View full text |Cite
|
Sign up to set email alerts
|

Polish version of the Intermittent Claudication Questionnaire

Abstract: Introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Leg pain while walking was reported by over 1/3 of the respondents. And although the average value of the ICQ questionnaire in the entire group, or even only in the PAD group, was low compared to critical limb ischaemia [11,28], what is worrying is the fact that symptomatic patients did not have any previous tests. These results also indicate non-compliance with the guidelines [2, 8-10], which recommend systematic foot examination at least once a year in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leg pain while walking was reported by over 1/3 of the respondents. And although the average value of the ICQ questionnaire in the entire group, or even only in the PAD group, was low compared to critical limb ischaemia [11,28], what is worrying is the fact that symptomatic patients did not have any previous tests. These results also indicate non-compliance with the guidelines [2, 8-10], which recommend systematic foot examination at least once a year in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, all subjects completed questionnaires assessing their expectations related to participation in the study, showing their attitude towards their own health condition and their specific quality of life related to the occurrence of symptoms of lower limb ischaemia. These were the following questionnaires, all in Polish: Intermittent Claudication Questionnaire (ICQ) [11], the patient request form questionnaire (PRF) [12,13], and the list of health criteria (LHZ) (Pl. lista kryteriów zdrowia -LKZ) [12].…”
Section: Methodsmentioning
confidence: 99%
“…Only recently, the Intermittent Claudication Questionnaire, a PAD -specific health -related quality of life (HRQoL) questionnaire was validated in Polish. 15 We selected another questionnaire specific to HRQoL in PAD, namely, the Vascular Quality of Life Questionnaire (VascuQol), because it covers not only a spectrum of claudication symptoms but also demonstrates good reliability in evaluating patients with CLTI, who frequently present at our center. 16 Characteristics of the VascuQol The VascuQol consists of 25 questions covering 5 domains: activities, symptoms, pain (physical domains), as well as emotions and social behavior (mental domains).…”
Section: Patients and Methods Linguistic Validationmentioning
confidence: 99%
“…Although recent efforts of Rosloniec et al15 have resulted in the first disease-specific HRQoL instrument for PAD that is validated in Polish, it would be not adequate for patients with CLTI, as they can barely walk 16. Literature reports and a review of available HRQoLs questionnaires indicated that the VascuQol is a robust tool for the assessment of the quality of life in PAD with a wide spectrum of clinical stages of the disease.…”
mentioning
confidence: 99%
“…We also used a specific tool to assess the quality of life of patients with PAD -the Polish version of the Intermittent Claudication Questionnaire (ICQ) [28]. The questionnaire consists of 16 questions assessing the impact of claudication on the functional capability of patients and health-related quality of life.…”
Section: Health-related Quality Of Life and Functional Statusmentioning
confidence: 99%